Effectiveness of psychosocial intervention enhancing resilience among war-affected children and the moderating role of family factors. (February 2015) - Diab, Marwan; Peltonen, Kirsi; Qouta, Samir R.; Palosaari, Esa; Punamäki, Raija-Leena
Abstract: The study examines, first, the effectiveness of a psychosocial intervention based on Teaching Recovery Techniques (TRT) to increase resiliency among Palestinian children, exposed to a major trauma of war. Second, it analyses the role of family factors (maternal attachment and family atmosphere) as moderating the intervention impacts on resilience. School classes in Gaza were randomized into intervention ( N = 242) and control ( N = 240) groups. The percentage of girls (49.4%) and boys (50.6%) were equal, and the child age was 10–13 years in both groups. Children reported positive indicators of their mental health (prosocial behaviour and psychosocial well-being) at baseline (T1), post-intervention (T2) and at a six-month follow-up (T3). At T1 they accounted their exposure to war trauma. Mothers reported about their willingness to serve as an attachment figure, and the child reported about the family atmosphere. Resilience was conceptualized as a presence of positive indications of mental health despite trauma exposure. Against our hypothesis, the intervention did not increase the level of resilience statistically significantly, nor was the effect of the intervention moderated by maternal attachment responses or family atmosphere.